Evaluation of the Integrated Service and Referral System Program in Poverty Alleviation In Bantaeng Regency - Yulianto, Arfah; Hamsu Abdul Gani; Rifdan, Rifdan (Socio-Economic and Humanistic Aspects for Township and Industry, 2024)
This study aims to determine the supporting and inhibiting factors in the Implementation of the integrated service and referral system program for poverty alleviation in Bantaeng Regency. This study uses the Convergent Parallel Design approach, which combines qualitative and quantitative methods. Data sources were obtained through in-depth interviews, observations, and surveys of stakeholders and program beneficiaries. Data analysis techniques involve SWOT analysis to identify strengths, weaknesses, opportunities, and threats in program implementation. The results of the study indicate that supporting factors for program implementation include local government commitment and community support. Meanwhile, inhibiting factors include limited Human Resources at the implementing level and challenges in providing accurate and real-time data.